Relationship between dimensions Of Corporate Social Responsibility (CSR) and corporate image: in Malaysian perspective / Muhammad Azree Danial Rozlan - Rozlan, Muhammad Azree Danial (Faculty of Business and Management, 2017)
It cannot be denied that issues on corporate image had increased tremendously in the past decade especially with the British Petroleum (BP) oil spill and the scandal of Enron. There has been much debate whether organizations should be socially responsible or not and to what extent they should be responsible. Thus, most organization started to improvise their corporate image through many forms and surprisingly, one of it was Corporate Social Responsibility (CSR). There are four dimensions of CSR namely, ethical, legal, economic and philanthropy responsibilities. The objective of this research is to examine the level of public understanding on corporate image and the strength of relationship between all the dimensions of CSR towards corporate image and to what extent the CSR dimensions influence corporate image. Therefore, the research is conducted in order to study the relationship between dimensions of Corporate Social Responsibility (CSR) and corporate image perceives through practices of CSR.